PENGARUH HARGA DAN CITRA TOKO TERHADAP LOYALITAS KONSUMEN DAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO NOVA DI SITUBONDO - Wijatmoko, Naufal; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing Strategy is an integrated comprehensive plan in the field of marketing and marketing targets in achieving company goals through a marketing mix that includes product, price, place and promotion strategies. The purpose of this study was to analyze and test the effect of marketing strategy on increasing product sales at Nova stores. The population in this study is Nova shop located in Situbondo. The sampling technique was determined by probability sampling technique with a simple random sampling method. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that price and store image have a significant positive effect on consumer satisfaction, price and store image have a significant positive effect on consumer loyalty, consumer satisfaction has a significant negative effect on consumer loyalty, price on consumer loyalty through satisfaction consumers have a significant negative effect, and store image on consumer loyalty through consumer satisfaction has a negative but not significant effect.